Vplyv dezinfekčného účinku P3 TOPAX 66 na hygienický režim v potravinárskej prevádzke - Veszelits Laktičová, Katarína; Vargová, Mária; Pošiváková, Terézia; Švajlenka, Jozef; Hromada, Rudolf; Cimboláková, Iveta; Koščová, Jana; Takáč, Ladislav (Chemické listy, 2017)
The aim of the article is to monitor the total numbers microorganisms, coliform bacteria and fungi located on the surface and in the air before, during and after disinfection with P3 Topax 66 in selected areas. Statistical analysis confirmed the efficacy of the P3 Topax 66 disinfectant in all of the three analyzed groups of microorganisms present on the surfaces and in the air with the exception of disinfection efficacy on air coliforms, which could not be shown due to the low detection sensitivity during monitoring.
Keywords: Disinfectants; Occupational Health; dezinfekce; Food Industry; hygiena práce; biofilmy; potravinářský průmysl; masný průmysl; Biofilms; Disinfection; Meat-Packing Industry; dezinficiencia